2016
DOI: 10.1245/s10434-016-5311-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Affordable Care Act on North Carolinian Breast Cancer Patients Seeking Financial Support for Treatment

Abstract: Background The Affordable Care Act (ACA) was instated on 23 March 2010 to improve healthcare quality, reduce costs, and increase access. The Pretty in Pink Foundation (PIPF), a non-profit 501(C)(3) organization in North Carolina, provides financial assistance and in-kind support to individuals seeking help with breast cancer care. The objective of this study was to determine whether sociodemographic variables and treatment services varied among PIPF recipients since enactment of the ACA. Methods North Caroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…However, recent single institution data out of California have suggested an increased number of Hispanic women accessing breast cancer care since ACA implementation . One study demonstrated a decrease in patients accessing non‐profit‐based assistance for breast cancer services, but no significant change in insurance status, suggesting that some patients remain underserved despite the ACA . A recent study demonstrated a reduction in uninsured breast cancer patients in Medicaid expansion states only …”
Section: Introductionsupporting
confidence: 93%
“…However, recent single institution data out of California have suggested an increased number of Hispanic women accessing breast cancer care since ACA implementation . One study demonstrated a decrease in patients accessing non‐profit‐based assistance for breast cancer services, but no significant change in insurance status, suggesting that some patients remain underserved despite the ACA . A recent study demonstrated a reduction in uninsured breast cancer patients in Medicaid expansion states only …”
Section: Introductionsupporting
confidence: 93%
“…Our findings are timely, given the increasing attention paid to developing financial support resources for cancer survivors overall [ 40 42 ]. Financial navigation and other types of interventions may be particularly useful for mitigating racial/ethnic disparities in PSS, given the large independent mediating role of SEP.…”
Section: Discussionmentioning
confidence: 99%
“…These patients continued to experience financial stress because of inadequate insurance coverage despite the changing national landscape. 48 The range of financial experiences captured in our study manifested in an observed discordance in responses between women's multiple-choice responses categorizing their financial hardship and open-ended narratives. These discrepant responses may be due to participants' desire to acknowledge their own financial privilege, leading them to select a financial burden level on their multiple-choice response that seemed less severe than the financial burdens their qualitative narratives would suggest.…”
Section: Discussionmentioning
confidence: 80%
“…These patients continued to experience financial stress because of inadequate insurance coverage despite the changing national landscape. 48…”
Section: Discussionmentioning
confidence: 99%